Historical contingency and path dependence in bottom-up democratisation through NGOs: a case study from Pakistan. Issue 7 (2nd October 2020) - Owais, Syed
ABSTRACT: This article presents an institutionalist account of historically structured formal and informal institutions and the politico-economic factors that influenced the efforts of a Pakistani NGO (FORDP) to democratise rural communities. Using interviews with FORDP staff members, the article demonstrates that its bottom-up democratisation has gradually succumbed to structures of inequality at the micro level and to macro politico-economic changes. At the macro level, Pakistan's alliance in the "war on terror" and the post-2005 earthquake relief efforts translated into large-scale NGO interventions at the grassroots. However, as these were patronage-based, they made it harder for FORDP to instil long-lasting change in communities.